Exploring the impact of landscape design on user preferences in shopping centers post the COVID-19 Pandemic - Aslantamer, Özlem Nur; Ilgın, Hüseyin Emre (Journal of design for resilience in architecture and planning : (Online), 2024)
This study explores the impact of landscape design, which has gained importance alongside architectural changes in shopping centers, and investigates preferences in the post-COVID-19 pandemic era. Although e-commerce has increased during the pandemic, research and societal behaviors suggest that shopping centers will continue to serve as contemporary agoras due to their socialization and leisure functions. However, in response to the pandemic, it is anticipated that newly designed shopping centers will be architecturally conceived as semi-outdoor or outdoor spaces, regardless of climate conditions. This transformation will involve the softening of rigid appearances through landscape elements, making them both ecologically and psychologically sustainable. The number of studies on this subject is limited. To address this knowledge gap, an online survey was conducted with 586 randomly selected users across nine shopping centers located in three major cities of Turkey: Istanbul, Ankara, and Izmir, with three shopping centers in each city. The survey investigated users' preferences for architectural styles (indoor, semi-outdoor, or outdoor) and landscape design in shopping centers. The findings of the study indicate that post-pandemic, outdoor and semi-outdoor shopping centers are likely to be preferred more frequently. An emphasis is likely to be placed on natural landscape elements such as plants and water features in landscape design. Furthermore, shopping center designs are likely to become simpler, offering comfortable and spacious navigation areas while optimizing parking and transportation conditions. This study is expected to shed light on decision-making processes for future shopping centers. By incorporating consumer preferences, architects can enhance the sustainability of shopping center investments through next-generation design.